Molecular Characterization of Neuroendocrine Carcinomas of the Endometrium: Representation in All 4 TCGA Groups. (November 2020) - Howitt, Brooke E.; Dong, Fei; Vivero, Marina; Shah, Varsha; Lindeman, Neal; Schoolmeester, J. Kenneth; Baltay, Michele; MacConaill, Laura; Sholl, Lynette M.; Nucci, Marisa R.; McCluggage, W. Glenn
Abstract : High-grade neuroendocrine carcinomas (NEC) of the endometrium are rare and account for <1% of all endometrial carcinomas. Both small cell neuroendocrine carcinoma (SCNEC) and large cell neuroendocrine carcinoma (LCNEC) morphologies have been reported. Little is known regarding the molecular features of endometrial NEC including how they compare to pulmonary NEC (the most common site for these neoplasms) and the more common endometrial carcinoma histotypes. In this study, we investigated the molecular alterations in a series of endometrial NEC using a targeted next generation sequencing panel (Oncopanel). Fourteen NEC were sequenced; pure NEC (n=4) and mixed (n=10) with endometrioid adenocarcinoma (n=9) or carcinosarcoma (n=1). The NEC components of mixed tumors comprised LCNEC (n=6) and SCNEC (n=4). The 4 pure NEC comprised LCNEC (n=2) and SCNEC (n=2). Molecular analysis classified tumors into the 4 The Cancer Genome Atlas groups: (1) POLE -mutated/ultramutated (1/14; 7%), (2) microsatellite instability/hypermutated (6/14; 43%), (3) TP53 mutated/copy number high (2/14; 14%), or (4) no specific molecular profile (5/14; 36%). Overall, 50% of cases were ultramutated or hypermutated. In 8 cases of mixed carcinomas, the different histologic components were macrodissected and separately sequenced; molecular alterations were nearly identical among the 2 components, with the non-NEC component harboring slightly increased tumor mutational burden. Only 2 carcinomas (both with pure SCNEC morphology) had a molecular profile that would be expected in typical pulmonary SCNEC ( RB1 deletion and TP53 mutations). Our findings, similar to data from NECs of other anatomic sites, suggest that the molecular context may be important when selecting therapies for women with endometrial NEC. Immune checkpoint inhibition may be a reasonable approach to treatment of microsatellite instability-NEC and we thus recommend that all endometrial NEC be tested for mismatch repair abnormalities, either molecularly or by mismatch repair protein immunohistochemistry.